Attitude of Postgraduate Diploma in Teaching (PGDT) Trainees towards the Teaching Profession in Ethiopia - Tensae Zeleke (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
This study explored the attitude of trainees in postgraduate diploma in teaching towards the teaching profession. The study had a descriptive survey design. Two hundred and fifty-eight trainees participated in the study. Proportionate stratified random and simple random sampling were used in the selection of the study participants. Quantitative data was collected using a standardized questionnaire developed by Renthlei and Malsawmi (2015). Percentages and Stanine scale frequency distributions were used to analyze the data and report the findings. The study revealed that a lack of other better job opportunities was the main reason for the trainees to choose teaching as their future profession. Most also expressed the interest to quit the training and join any other better job opportunity the moment they get the chance. Overall, the majority had a low attitude towards teaching as a profession. Such a low trainees' attitude towards teaching and their intention to quit the training or leave the profession any time the opportunity comes their way, puts the government's plan to expand the coverage of education in jeopardy. Clearly, an increase in schools cannot be achieved without a parallel increase in the number of qualified teachers. Finally, implications of the findings were forwarded to pertinent bodies in teacher education programs.